PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DAN DANA ALOKASI UMUM TERHADAP BELANJA DAERAH - Rosiana, Eryza; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Local expenditure is all local expenditures in a one fiscal year. One of the sectors which have anopportunity to finance the local expenditure is local tax, local retribution, and general allocation fund. Thepurpose of this research is to find out whether local tax, local retribution, and general allocation fund haveinfluence to the Allocation of Local Expenditure in districts / cities in East Java. The population and sample is alldistricts / cities in East Java. This research has been conducted by using multiple linear regressions analysis andthe data has been obtained from the summary of the report of the realization of Local Budget from 2011 to 2013in the SAP format which has been published by East Java Statistics Indonesia. In which the sample selection hasbeen done by using full sampling technique and 114 samples have been selected for further analysis. The result ofthe research shows that local tax, local retribution, and general allocation fund have significant influence to theallocation of local budget indistricts/ cities in East Java, it can be explained in the Adjusted R Square value0.750 which means that 75% from dependent variable of Local Budget which can be explained by the variation ofindependent variables i.e. Local Tax (PD), Local Retribution (RD), General Allocation Fund (DAU).Meanwhile, the remaining 25% is influenced by other factors. Partially, local tax, local retribution, and generalallocation fund have significant influence to the Allocation of Local Expenditure.Keywords: Local Tax, Local Retribution, and General Allocation Fund, Local Expenditure.